A review of carotenoid utilisation and function in crustacean aquaculture. (16th September 2015) - Wade, Nicholas M.; Gabaudan, Jacques; Glencross, Brett D.
Abstract: Crustaceans are cultured extensively around the world in intensive farming systems. High‐performance formulated feeds have been developed for crustacean aquaculture, which are often supplemented with a number of natural and synthetic carotenoid sources. Studies over a number of years have consistently shown that dietary carotenoid supplementation is beneficial for crustacean aquaculture across a range of commercially relevant parameters. Most obvious is the effect on pigmentation, where carotenoid inclusion levels in feeds and duration of feeding diets with carotenoids have been optimised across many species to improve product colour, and subsequently quality and price. However, beneficial effects of carotenoid inclusion have increasingly been demonstrated on other parameters. This review updates the recent progress in our understanding of dietary carotenoid utilisation and storage, and the combined effects of diet, genetics and environment on crustacean pigmentation. In addition, the range of other physiological benefits this class of molecules brings to these animals is summarised. These include improvements in survival, growth, reproductive capacity, disease resistance and stress resistance.